Pre-school multilingualism : experiences from a national project in Norway - Sundelin, Marit (2011)
I will refer to a national project in Norway; initiated by NAFO, the National Center of Multicultural Education. In the period of 2007-2010 I was supervisor for 20 pre-schools in 5 different municipalities in the county of Troms, Norway. These pre-schools all had bilingual immigrant children, and were interested in learning more about both cultural diversity and multilingualism. This presentation will point out some of the development that took place in the staff of these pre-schools, and also focus on my work at the teacher education. How do my knowledge about pre-school and the theme multilingualism infect my teaching, and how can I prepare students working with bilingual children and improving their language skills? In this project, bilingual immigrant children are recognized as children with other first languages than Norwegian, Sami, Swedish, Danish or English. These children will learn Norwegian as their second language, and the pre-school teachers will play an important role in their language development. According to Kindergarten Act this group of children has the right to extra support, aiming to improve their Norwegian skills. The pre-school is required to encourage bilingual children’s use of their mother tongue, and simultaneously actively promote children’s development of Norwegian language skills (KD 2006). During this project period I mean to have seen a pattern and a development in the preschools work with bilingual children. This could help other preschools focusing on the same challenges. I will also focus on the role of the preschool teacher education preparing their students to their work with bilingual immigrant children.